1986
DOI: 10.1159/000146166
|View full text |Cite
|
Sign up to set email alerts
|

Systematisation of the Arteries in the Splenic Hilus

Abstract: 156 abdominal preparations were explored by arteriography, corrosion and dissection. Within the meanders of the splenic artery a basic pattern can be traced. The division of the artery can easily be summarized by introducing the term of a truncus lienogastroepiploicus. The short gastric arteries are always present, and usually they are longer and more important than may appear from their name. In nearly half of the preparations (52%) an artery for the extremitas lienalis posterior is found; an artery for the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 7 publications
0
10
0
4
Order By: Relevance
“…It usually arises from the cranial border of the proximal half of the splenic artery, measuring about 1.5–3 mm in diameter (4–7). The posterior gastric artery courses upward posteriorly in an oblique direction, to the parietal peritoneum of the lesser sac, where it raises a fold before supplying the proximal posterior gastric wall (4–11). In some cases, it may also supply the distal esophagus and the spleen (forming an upper polar splenic artery) (6, 12).…”
Section: Discussionmentioning
confidence: 99%
“…It usually arises from the cranial border of the proximal half of the splenic artery, measuring about 1.5–3 mm in diameter (4–7). The posterior gastric artery courses upward posteriorly in an oblique direction, to the parietal peritoneum of the lesser sac, where it raises a fold before supplying the proximal posterior gastric wall (4–11). In some cases, it may also supply the distal esophagus and the spleen (forming an upper polar splenic artery) (6, 12).…”
Section: Discussionmentioning
confidence: 99%
“…Mikhail and Garcia-Porrero reported that splenic artery could give off one superior polar, one to three inferior polar, two (superior, inferior) or three (superior, medial, inferior) terminal (primary) segmental branches (Mikhail, 1979;Garcia-Porrero, 1988). Vandamme and Redmond reported that splenic artery was divided into one superior polar, two central (superior, inferior) and one inferior polar branches and each of them supplied their segments of spleen (Vandamme et al , 1986;Redmond et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by slight tissue shrinkage produced by formalin fixation in cadavers (Larsen et at., 2003). Vandamme and Bonte (1986) described the splenic artery to be composed of four anatomical divisions, including suprapancreatic, pancreatic, prepancreatic and prehilar segments. Moreover, Waizer et al (1989) reported the lengths of these splenic arterial segments to be 2.5, 10.5,2.5 and 1.5 em respectively.…”
Section: Serial Numbermentioning
confidence: 99%